Q: What is 6t-2t plus 5u?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5u + 2 = -185u = -20u = -4

2u + 1 = 5u + 5 2u - 5u = 5 - 1 -3u = 4 3u = -4 u = -4/3

3u - 5u= - 2u=====

No. It is a sum of four terms which can be simplified to a sum of three terms.

23

Related questions

5u + 2 = -185u = -20u = -4

2u + 1 = 5u + 5 2u - 5u = 5 - 1 -3u = 4 3u = -4 u = -4/3

Do you mean 5u-10 = u+46? If so then:- 5u-10 = u+46 5u-u = 46+10 4u = 56 u = 14

23 + 5u = 17Subtract 17 23 from both sides:5u = -6Divide both sides by 5:u = -6/5

r = 5k + 5ur - 5u = 5kk = r/5 - u

If you mean: 5u+10 = u+46 Then the value of u is 9

-5u + 4 + 8u = 43simplify by subtracting 4 from both sides of the equation to get rid of the 4 on the left:-5u + 8u = 43Simplify further by combining the -5u and the 8u:3u = 43Divide both sides by 3 to solve for u:u = 43/3rewrite the fraction:u = 14 1/3

No. It is a sum of four terms which can be simplified to a sum of three terms.

3u - 5u= - 2u=====

23

(9 - 5u)(9 + 5u)

5(u-5)